Dynamics of poor health and non-employment - Peter Haan; Michał Myck (Institute for the Study of Labor (IZA), 2009)
While there is little doubt that the probability of poor health increases with age, and that less healthy people face a more difficult situation on the labour market, the precise relationship between facing the risks of health deterioration and labour market instability is not well understood. Using twelve years of data from the German Socio-Economic Panel we study the nature of the relationship between poor health and non-employment on a sample of German men aged 30-59. We propose to model poor health and non-employment as interrelated risks determined within a dynamic structure conditional on a set of individual characteristics. Applying dynamic panel estimation we identify the mechanism through which poor health contributes to the probability of being jobless and vice versa. We find an important role of unobserved heterogeneity and evidence for correlation in the unobservable characteristics determining the two processes. The results also show strong persistence in the dynamics of poor health and non-employment.
urn:nbn:de:101:1-20090513520
Keywords: C33; J21; J14; 330; Health; non-employment; risk; ageing; dynamic panel data; Gesundheit; Altersgruppe; Arbeitslosigkeit; Arbeitsplatzsicherung; Panel; Deutschland